2013
DOI: 10.1128/jvi.03222-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Role for the trans -Golgi Network in Human Papillomavirus 16 Pseudovirus Infection

Abstract: Human papillomavirus 16 (HPV16) enters its host cells by a process that most closely resembles macropinocytosis. Uncoating occurs during passage through the endosomal compartment, and the low pH encountered in this environment is essential for infection. Furin cleavage of the minor capsid protein, L2, and cyclophilin B-mediated separation of L2 and the viral genome from the major capsid protein, L1, are necessary for escape from the late endosome (LE). Following this exodus, L2 and the genome are found colocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
176
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(191 citation statements)
references
References 54 publications
(57 reference statements)
8
176
4
3
Order By: Relevance
“…We identified that disruption of the TGN with Exo2 significantly reduced nuclear translocation of viral DNA, suggesting the TGN plays a critical role in this nuclear translocation pathway in monocytes. Human papilloma virus also has been reported to use the TGN during entry, although the specific aspects of how this nonenveloped virus moves to the nucleus are not known (32). Our data show that HCMV then sequentially travels from the TGN to Rab11 + recycling endosomes before nuclear translocation.…”
Section: Discussionmentioning
confidence: 50%
“…We identified that disruption of the TGN with Exo2 significantly reduced nuclear translocation of viral DNA, suggesting the TGN plays a critical role in this nuclear translocation pathway in monocytes. Human papilloma virus also has been reported to use the TGN during entry, although the specific aspects of how this nonenveloped virus moves to the nucleus are not known (32). Our data show that HCMV then sequentially travels from the TGN to Rab11 + recycling endosomes before nuclear translocation.…”
Section: Discussionmentioning
confidence: 50%
“…The tools and approaches used here may reveal that other viruses also use this trafficking pathway. After this work was completed, another laboratory also implicated the TGN in HPV16 entry (38).…”
Section: Discussionmentioning
confidence: 99%
“…Host cell cyclophilins release the majority of L1 from the L2 protein, which remains in complex with the viral genome (2,23,24). A large portion of the L2 protein translocates across the endocytic membrane to engage factors, including the retromer complex, dynein, sorting nexins, and rab GTPases, that mediate transport to the trans-Golgi network (TGN) (25)(26)(27)(28)(29)(30)(31)(32)(33)). An siRNA screen has suggested that nuclear pore complexes are not required for nuclear entry, but that nuclear envelope breakdown during mitosis is necessary (34,35).…”
mentioning
confidence: 99%